Mecanismos discursivos de promoción de eventos en la Web: los titulares de las Expos (Altre Modernità, 2012)
This paper is in line with a national research project (PRIN) about the Language of Tourism in Spanish and Italian: Lexical, Pragmatic and Intercultural Aspects. Our aim is to contribute to the study of digital tourist texts adopting a methodological perspective based on the most recent studies about the rhetoric of advertising, web advertising and institutional communication. We carry out a contrastive analysis of the headlines introducing news and press releases published on line within five promotional and touristic websites, those of the expositions of Sevilla (1992), Zaragoza (2008), Shanghai (2010, Italian pavilion), Shanghai (2010, Spanish pavilion), and Milan (2015).